The Relationship Between Real U.S. Treasury Yields and Equity Fund Flows - Sillanpää, Eetu (My University, 2026)
This thesis aims to examine the relationship between U.S. real Treasury yields and equity fund flows. The thesis goal is to observe this link through various variables, while mostly focusing on behavioural aspects. This thesis is constructed around existing literature and established theoretical frameworks in finance. Existing literature and theoretical frameworks include the Fisher relation, modern portfolio theory, asset-substitution logic, monetary-policy transmission, liquidity constraints, and behavioural finance. Through a full analysis and interpretation of these recent findings, the thesis presents the results and evaluates how the yield-flow link can depend on the measurement style used, underlying drivers, as well as the broader macro-financial environment. The results are summarised by integrating the empirical and theoretical base into one clear integrated framework and making propositions from them. This thesis review especially emphasises the behavioural factors, such as nominal framing and money illusion, which can help us to obtain more concrete evidence on how investors interpret these macroeconomic signals. In conclusion, based on previous literature, the relationship is conditional, but there is evidence that real yields can truly influence equity fund flows. Real yields tend to matter mainly indirectly through the broader discount-rate environment and not as a fully stand-alone proxy for investors to follow. This is most likely caused by various factors that affect this relationship individually and simultaneously.

Tämän tutkielman tavoitteena on tarkastella Yhdysvaltain reaalisten valtionlainatuottojen ja osakerahastovirtojen välistä suhdetta. Tutkielman tarkoituksena on havainnoida tätä yhteyttä useiden eri muuttujien kautta, painottaen erityisesti käyttäytymistaloustieteellisiä näkökulmia. Tutkielma rakentuu olemassa olevan kirjallisuuden ja vakiintuneiden rahoitusteoreettisten viitekehysten ympärille. Näihin kuuluvat Fisherin relaatio, moderni portfolioteoria, varallisuuserien substituutiologiikka, rahapolitiikan välittymismekanismi, likviditeettirajoitteet sekä käyttäytymisrahoitus. Viimeaikaisen tutkimuskirjallisuuden kattavan analyysin ja tulkinnan kautta tutkielma esittelee tulokset ja arvioi, kuinka korko-virtaussuhde voi riippua käytetystä mittaustavasta, taustalla vaikuttavista tekijöistä sekä laajemmasta makrotaloudellisesta ja rahoituksellisesta ympäristöstä. Tulokset tiivistetään yhdistämällä empiirinen ja teoreettinen perusta yhdeksi selkeäksi kokonaisvaltaiseksi viitekehykseksi sekä muodostamalla niiden pohjalta johtopäätöksiä. Tutkielmakatsaus korostaa erityisesti käyttäytymistekijöitä, kuten nimellistä kehystämistä ja rahailluusiota, jotka voivat auttaa saamaan konkreettisempaa näyttöä siitä, kuinka sijoittajat tulkitsevat näitä makrotaloudellisia signaaleja. Johtopäätöksenä voidaan todeta, että aiemman kirjallisuuden perusteella suhde on ehdollinen, mutta näyttöä löytyy siitä, että reaalituotot voivat aidosti vaikuttaa osakerahastovirtoihin. Reaalituottojen merkitys näyttäisi kuitenkin olevan pääasiassa epäsuoraa laajemman diskonttokorkoympäristön kautta, eikä niitä seurata täysin itsenäisenä sijoittajien käyttämänä indikaattorina. Tämä johtuu todennäköisesti useista tekijöistä, jotka vaikuttavat tähän suhteeseen sekä yksittäin että samanaikaisesti.
Keywords: finance; security market; monetary policy; financial markets; investors; investments (economics); mutual funds; funds (organisations); behaviour; monetary policy; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|